Identification of Angiotensin Receptor Blocker II Ligands from Gotu Kola (Centella asiatica L.) Extract: an In Silico Study - Dinata, Deden Indra (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Non-communicable diseases, including hypertension, are a significant source of health issues in developed nations[MOU1] . Angiotensin II Receptor Blocker (ARB) is frequently used as the first-line treatment for hypertension. ARB works by inhibiting Angiotensin II which can cause vasoconstriction of entire blood vessels[l2] . This study aimed to find lead compound of 54 compounds obtained from gotu kola (Centella asiatica L.) in order to determine the antihypertensive activity. The target of drug action chosen in this study was the type 1 angiotensin II receptors (AT1). Molecular docking and molecular dynamics simulation were chosen as the methods in this study to predict the interaction and the affinity and stability of the interaction. Based on the results of molecular docking, it was found that the compound of campesterol, centellasaponin B, and corosolic acid gave good affinity to the targets. The test ligand that the Ki and DG values were close to the natural ligand (Olmesartan) campesterol with a value of -10.79 kcal/mol and 12.28 nM. Meanwhile, in the molecular dynamics simulation test, it was found that corosolic acid has good interaction stability with the targets and was constant from the beginning of the simulation to 100 ns, while for MMGBSA centellasaponin B the lowest total energy value was -71.4347 kcal/mol. It was concluded that the gotu kola (Centella asiatica L.), compound corosolic acid, and centellasaponin B had the potential as a lead compound that had affinity and stability for the interaction with the AT1 receptor as antihypertensives.